A Privacy-Preserving Attribute-Based Encryption System for Data Sharing in Smart Cities. (8th October 2021) - Shen, Xieyang; Huang, Chuanhe; Wang, Danxin; Shi, Jiaoli
Abstract : Information leakage and efficiency are the two main concerns of data sharing in cloud-aided IoT. The main problem is that smart devices cannot afford both energy and computation costs and tend to outsource data to a cloud server. Furthermore, most schemes focus on preserving the data stored in the cloud but omitting the access policy is typically stored in unencrypted form. In this paper, we proposed a fine-grained data access control scheme based on CP-ABE to implement access policies with a greater degree of expressiveness as well as hidden policies from curious cloud service providers. Moreover, to mitigate the extra computation cost generated by complex policies, an outsourcing service for decryption can be used by data users. Further experiments and extensive analysis show that we significantly decrease the communication and computation overhead while providing a high-level security scheme compared with the existing schemes.